2015
DOI: 10.1007/s12011-015-0283-x
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Markers and Histological Analysis in Diverse Organs from Rats Treated with a Hepatotoxic Dose of Cr(VI): Effect of Curcumin

Abstract: Hexavalent chromium [Cr(VI)] compounds are extremely toxic and carcinogenic. Despite the vast quantity of reports about Cr(VI) toxicity, the information regarding its effects when it is intraperitoneally (i.p.) administered is still limited. In contrast, it has been shown that curcumin prevents hepatotoxicity induced by a single intraperitoneal injection of 15 mg/kg body weight (b.w.) of potassium dichromate (K2Cr2O7). This study aims to evaluate oxidative stress markers, the activity of antioxidant enzymes, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
14
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(18 citation statements)
references
References 66 publications
4
14
0
Order By: Relevance
“…In Swiss mice poisoned with prooxidative lead acetate, it was observed that curcumin has positive effects at the level of neurotransmitters in the hippocampus, where increased levels of serotonin and decreased levels of dopamine were reported, while no such effects were observed in the striatum [151]. Similar results were observed in the brains of rats poisoned with K 2 Cr 2 O 7 [102] and (CH 3 COO) 2 Pb [101].…”
Section: Phenolic Compoundssupporting
confidence: 59%
“…In Swiss mice poisoned with prooxidative lead acetate, it was observed that curcumin has positive effects at the level of neurotransmitters in the hippocampus, where increased levels of serotonin and decreased levels of dopamine were reported, while no such effects were observed in the striatum [151]. Similar results were observed in the brains of rats poisoned with K 2 Cr 2 O 7 [102] and (CH 3 COO) 2 Pb [101].…”
Section: Phenolic Compoundssupporting
confidence: 59%
“…These results are congruent with the research accomplished by García-Niño et al (2015), who analyzed the effects of Cr (VI) in the kidneys and confirmed the study of Tagliari, Vargas, Zimiani, and Cecchini (2004), in which the rats' livers were investigated and, in both studies, there was no increase in the levels of MDA. However, these studies were accomplished with acute exposures and intraperitoneal injections of Cr (VI), differently from our study, in which we used chronic exposure and contamination of water with Cr (VI) in an animal model.…”
Section: Discussionsupporting
confidence: 89%
“…It should be noted that most of the studies above-mentioned (Tagliari et al, 2004;Parveen et al, 2009;Balakrishnan et al, 2013;García-Niño et al, 2015) were performed with acute exposures and by injections, either intraperitoneal or subcutaneous. Our study, however, was accomplished by chronic treatment and oral exposure with water ad libitum, and it obtained significant results that corroborate to studies with another exposure route.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies demonstrate that numerous inflammatory cytokines are produced in hepatotoxic liver tissues ( 7 ). In addition, oxidative damage is considered as a mechanism that contributes to the initiation and progression of hepatic damage in a variety of liver disorders ( 8 , 9 ). Therefore, anti-inflammatory drugs and antioxidants obtained from plants represent a logical therapeutic strategy for the treatment of liver diseases.…”
Section: Introductionmentioning
confidence: 99%